"\\frac{d^2y(x)}{dx^2}-9y(x)=e"
The general solution will be the sum of the complimentary solution and particular solution.
The complimentary solution:
"\\frac{d^2y(x)}{dx^2}-9y(x)=0"
Solution will be proportional for ekx for some constant k.
Substitute y(x)= ekx into equalation.
k2ekx-9ekx=0
ekx(k2-9)=0
As ekx can not be equal 0, so k2-9=0
k1=3, k2=-3
The complimentary solution is
y(x)=C1e3x+C2e-3x
Particular solution:
y(x)=Be3x
y''=9Be3x
-9Be3x=e
"B=\\frac{-e}{9e^{3x}}"
y(x)=-e/9
Answer:y(x)=C1e3x+C2e-3x-e/9
Comments
Leave a comment